Student Perception on Biology Subject Using Virtual Laboratory - Elania Zoela Saputri; Much Fuad Saifuddin (Indonesian Journal of Biology Education, 2021)
The virtual laboratory plays an essential role in providing visualization of a process in the biological sciences, thus helping students understand biology learning. This study aims to determine students' perceptions at SMPN 15 Yogyakarta on the use of Virtual Laboratory (V-Lab) Biology developed by the Ministry of Education and Culture. This research is a quantitative descriptive study using a questionnaire technique. The data collection instrument is in the form of a questionnaire. The population of this study was students of class VIII odd semester in the 2021/2022 academic year at SMPN 15 Yogyakarta. The number of research subjects as many as 23 students in class VIII D SMPN 15 Yogyakarta. Data analysis was carried out using a Likert scale through 10 statement items related to the use of V-Lab. The results showed that most students gave a positive perception with a percentage range (39-75%). The student has a positive perception of V-Lab and can be an alternative to be used primarily in online learning.